Electrifying Decisions: Consumer Attitudes and Adoption Drivers in India's EV Boom - Rajak, Priyanka; Sharma, Akshita (Journal of Ecohumanism, 2024)
This paper will examine how the knowledge of the environment among individuals influences the decision and adoption of Electric Vehicles (EVs). It has been oriented on the positive side of nature and the transition of simple usefulness into eco-friendly usefulness. The primary objective of this piece of work is to learn the level of opinion of the people concerning self driving capabilities and vehicle tracking services. It, too, provides the reasons why individuals embrace new technology and offers simple recommendations to facilitate the global expansion of EVs. Six primary points that include Charging Time, New Technology, Believed Quality, Believed Cost, Knowledge Level, and Comfort were factor analyzed in this research. The results indicate that such aspects as customer loyalty, saving of energy, charging networks, and customer authorization are fairly impactful. This implies that such points play a critical role in determining the way buyers choose to use EVs.